Transformers Energon : Megatron returns - Donkin, Andrew (London ; New York : DK Pub., 2005)
Alpha-Q hopes that by bringing Megatron back to life, he will have an ally in his effort to reawaken the evil Unicron, but Megatron has plans of his own and will let nothing stand in his way.
Includes index.
Accelerated Reader AR
Keywords: Science fiction